Levels of media planning in the international community - BRlAH, ALAA ADHAB; QASM, KARRAR RASHD (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
In the second half of the twentieth century, the world witnessed an expansion towards science and planning in various aspects of life, which led to the necessity of thinking about communications planning as an integral part of this general development. This was evident in the use of communications as an essential tool within development and progress strategies. In the course of the development of this planning, communication experts believe that it passed through two main stages. The first stage is called partial communication planning, as societies in that period focused on using communications in partial plans to develop areas such as agricultural extension, expanding the scope and quality of government services, strengthening and improving education systems, developing mass means of communication, and expanding the scope and services of wired communications. As for the second stage, it is known as the comprehensive communication planning stage, where it deals with current and future events and transformations with all the capabilities and capabilities required, with the aim of achieving stability and development in societies.